Resisting the Untainted Lie: Rebellion and False Utopianism in The Scorch Trials - Nawaful Raekhan (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
This article analyzes James Dashners The Scorch Trials by placing it within Tom Moylans framework of critical dystopian literature. It shows how WICKEDs utopian language masks genuinely oppressive practices and maps the narrative signs that still leave room for revolt. Through close reading and concept-driven interpretation, the study traces Moylans notions of the utopian mask, counter-memory, and critical hope, highlighting the tensions between WICKEDs propaganda, the scorched landscape, and the Gladers fragmented recollections and covert defiance. Results indicate that the novel exposes the gap between WICKEDs redemptive claims and its brutal methods while keeping open the prospect of brighter futures steered by individual and collective action. In doing so, the text delivers a sharp critique of biopolitical governance, ecological ruin, and weaponized optimism, echoing warnings found in present-day debates about authoritarian politics and crisis capitalism. By testing Moylans concepts within young adult fiction, the article broadens dystopian studies, affirms the genres power to interrogate hierarchies, and illustrates how narratives for younger readers still imagine plausible sites of resistance.